Dynamics of Slovenian Entrepreneurship: Slovenian Entrepreneurship Observatory 2008 (University of Maribor Press, 2009)
Part one presented the Slovenian entrepreneurial landscape in the year 2007. The second part compared Slovenian and EU-27 economy on various indicators. Part three analysed the process of firm entries in Slovenia while controlling for the specificities of regions and time, from 2000 to 2005. The fifth part analysed the impact of technical and cost efficiencies on firms’ income position and the relationship between supply and demand. The analysis examined tourism firms in Slovenia. The sixth part dealt with regional analysis of the early-stage entrepreneurship in Slovenia. The aim was to gain insight into developmental particularities of Slovenian family businesses and institutional support offered to family businesses in Slovenia. The seventh part examined different reasons for outsourcing according to strategic and traditional reasons. Lastly, we examined networking activities between enterprises and entrepreneurs. The empirical research revealed there are certain differences among Slovene SMEs according to their company size and gender.